Stres di kalangan guru wanita yang mengajar mata pelajaran Kemahiran Hidup - Yaakub, Noran Fauziah; Lope Pihie, Zaidatol Akmaliah; Mahyuddin, Rahil (Universiti Putra Malaysia Press, 2001)
A study was conducted on women teachers from the Hulu Langat District, Selangor Darul Ehsan, who were teaching the Living Skills subject. The objectives of the study were a) to determine the stress level of the teachers and b) to explain stress in terms of the independent variables, work load and the student factor. Through the open ended questions, other factors that might cause stress were looked into. The findings showed that 50% of the respondents belonged to the non stress category while the other 50% were stressful. By utilizing the regression analysis, it was found that 72% of the variance was due to work load and the student factor. The results of this study had several implications on how to overcome stress in general among teachers.